Stabilization of solutions to the initial boundary–value problems for quasilinear parabolic equations - Tedeev, A. F. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Lower bounds are obtained for solutions of the initial–boundary Dirichlet problem for high order equations. Sharp bounds are also obtained for $ess sup| abla u(x,t)|$ of the Neumann initial–boundary problem for a second order equation in $D=Ω × (t>0)$, where $Ω \subset R^n$, $n≥ 2$ is a domain with noncompact convex boundary.